Anthropometric and functional characteristics of phisically active individuals (2008)
In order to determine their health status and physical fitness, studies were carried out in 57 women and 60 men, aged between 45 and 77 years, registered in a physical activity program in Cali, Colombia. We report the results of the anthropometric and functional tests. Measurements of weight and height were used to calculate the Body Mass Index (BMI). Functional studies included power and flexibility tests as well as an incremental test in cyclergometer to evaluate the maximum oxygen consumption which, along with the Mets, would classify the functional capacity. Average results were as follows: age 51.4 ± 6.4 years; height 165 ± 9.2 cm; body weight 72.0 ± 13.4 kg; BMI 26.6 ± 3.4 kg/m2; maximum oxygen consumption 26.5 ± 9.0 mL/kg/min; Mets 7.6 ± 2.6; anaerobic power 70.6 ± 39.6 kg/seg and flexibility, evaluated with the Sit and Reach test, 23.3 ± 10.7 cm. Due to the reduced number of individuals studied, our data can not be extrapolated to the general Colombian population, but they may be the basis for other studies that characterize it from the anthropometrical and functional points of view.